Anaemia and coronary microvascular dysfunction in end-stage renal disease. (8th February 2021) - Radhakrishnan, A; Pickup, LC; Price, AM; Law, JP; Mcgee, KC; Fabritz, L; Senior, R; Steeds, RP; Ferro, CJ; Townend, JN
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): (1) University Hospitals Birmingham Charity (2) Metchley Park Medical Society Introduction:   Coronary microvascular dysfunction (CMD) is common among patients with end-stage renal disease (ESRD) and confers poor prognosis. Coronary flow velocity reserve (CFVR) is a marker of coronary microvascular function and can be reliably measured using Doppler echocardiography. Reduced CFVR in ESRD has been attributed to factors such as hypertension and left ventricular hypertrophy (LVH). Anaemia is prevalent in ESRD but the association between haemoglobin and CFVR in ESRD has not been studied.  Purpose:   To assess if CFVR is related to haemoglobin among patients with ESRD.  Methods:   22 subjects with ESRD and awaiting kidney transplant (8 pre-dialysis and 14 on peritoneal dialysis) were studied with adenosine myocardial contrast echocardiography, Doppler CFVR assessment and serum multiplex immunoassay analysis. Individuals with diabetes, uncontrolled hypertension or ischaemic heart disease were excluded. Results   7/22 (32%) of subjects had CMD (defined as CFVR <2). Age (47 years ± 15 vs 55 ± 10, p = 0.177), estimated glomerular filtration rate [7ml/min/1.73m² (5-11) vs 9 (7-10), p = 0.837], systolic blood pressure (129mmHg ± 25 vs 137 ± 20, p = 0.398) and left ventricular mass index (98g/m² ± 31 vs 98 ± 28, p = 0.936) did not significantly differ between subjects with or without CMD. There were no significant differences in other demographic, haemodynamic, laboratory or echocardiographic variables between the two groups.  A panel of biomarkers of inflammation, myocardial stretch, cardiac fibrosis and LVH studied by multiplex immunoassay also did not show any significant differences between the two groups. No subjects had wall motion abnormalities or perfusion defects on myocardial contrast echocardiography. CFVR was significantly lower in subjects with CMD (1.6 ± 0.2 vs 3.2 ± 0.9, p < 0.001). Subjects with CMD had significantly lower haemoglobin than subjects without CMD (102g/L ± 12 vs 117g/L ± 11, p = 0.008). There was a moderate positive correlation between haemoglobin and CFVR (r = 0.65, p = 0.001) – figure 1. In a stepwise multiple regression model with CFVR as the dependent variable and age, haemoglobin, systolic blood pressure, left ventricular mass index and estimated glomerular filtration rate as independent variables, only haemoglobin was an independent predictor of CFVR (β=0.051 95%CI 0.023-0.079, p = 0.001).  Conclusions   Among our cohort of ESRD patients awaiting kidney transplant, there was a high prevalence of CMD despite well controlled blood pressure and no significant LVH. Subjects with CMD had significantly lower haemoglobin than subjects without CMD. Reduced haemoglobin causes impaired oxygen carrying capacity to the myocardium, which may lead to microvascular ischaemia and adverse microvascular remodelling, causing CMD. Thus, anaemia may be a potentially correctible driver of CMD in ESRD.  This association needs to be confirmed in larger studies.